NucTools: analysis of chromatin feature occupancy profiles from high-throughput sequencing data - Vainshtein, Yevhen; Rippe, Karsten; Teif, Vladimir (BMC genomics, 2017)
Biomedical applications of high-throughput sequencing methods generate a vast amount of data in which numerous chromatin features are mapped along the genome. The results are frequently analysed by creating binary data sets that link the presence/absence of a given feature to specific genomic loci. However, the nucleosome occupancy or chromatin accessibility landscape is essentially continuous. It is currently a challenge in the field to cope with continuous distributions of deep sequencing chromatin readouts and to integrate the different types of discrete chromatin features to reveal linkages between them.
Gesehen am 12.09.2018